Practical Workflow for Cardiovascular Assessment and Follow-Up in Kawasaki Disease Based on Expert Opinion - van Stijn, Diana; Planken, R. Nils; Groenink, Maarten; Blom, Nico; de Winter, Robbert J.; Kuijpers, Taco; Kuipers, Irene (Frontiers in Pediatrics, 2022)
ABSTRACT BACKGROUND— Approximately 25% of the patients with a history of Kawasaki disease (KD) develop coronary artery pathology if left untreated, with coronary artery aneurysms (CAA) as an early hallmark. Depending on the severity of CAAs, these patients are at risk of myocardial ischemia, infarction and sudden death. In order to reduce cardiac complications it is crucial to accurately identify patients with coronary artery pathology by an integrated cardiovascular program, tailored to the severity of the existing coronary artery pathology. METHODS—The development of this practical workflow for the cardiovascular assessment of KD patients involve expert opinions of pediatric cardiologists, infectious disease specialists and radiology experts with clinical experience in a tertiary KD reference center of more than 1000 KD patients. Literature was analyzed and an overview of the currently most used guidelines is given. CONCLUSIONS— We present a patient-specific step-by-step, integrated cardiovascular follow-up approach based on expert opinion of a multidisciplinary panel with expertise in KD.